Faktor-Faktor Yang Berhubungan Dengan Perilaku Ibu Rumah Tangga Dalam Pengelolaan Sampah Berbasis 3R (Reduce, Reuse, Recycle) - Etika Sari; Intan Bahrina (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
Most waste generation is found in the surrounding environment,  from household waste and the increasing waste needs to be managed starting from the household level. Housewives' behavior in 3R-based waste management (Reduce, Reuse and Recycle) is influenced by several factors such as knowledge, attitudes and education. The aim of this research is to determine the factors related to housewives' behavior in 3R-based waste management. This type of research is analytical observational research with a cross sectional design. The population of this research is all housewives in Pondok Kemuning Village, totaling 450 housewives. The sample for this research consisted of 52 respondents. Data analysis used the chi-square test. The research results show that the factors related to 3R-based waste management behavior using bivariate analysis are knowledge (p-value 0.004), attitude (p-value 0.03), and education (p-value 0.03). Therefore, education and training activities related to waste management are carried out for the community, especially using the 3R concept method (Reduce, Reuse and Recycle) which is easy to apply on a household scale so that it can minimize waste generation and increase skills and knowledge in the community..